Disclosing strain: How psychosocial risk factors influence work-related musculoskeletal disorders in healthcare workers preceding and during the COVID-19 pandemic - Barros, Carla (2024)
Healthcare workers, particularly nurses, engage in a daily work routine that takes a toll on their emotional well-being, rendering them vulnerable to psychosocial risk factors. This research seeks to analyse the influence of psychosocial risk factors on the occurrence of work-related musculoskeletal disorders among nurses. An additional analysis was performed to understand the role of age in work-related musculoskeletal disorders and the perception of psychosocial risk factors. The study was conducted during two separate periods—pre-pandemic and pandemic times—involving a sample of 456 nurses from both public and private hospitals in Portugal. The INSAT—Health and Work Survey—was used as measuring instrument. The primary observations indicated a consistency between psychosocial risk factors and the occurrence of work-related musculoskeletal disorders. The findings revealed a significant exposure to psychosocial risk factors, with work pace, intensity, work relationships, and emotional demands exhibiting higher global average percentages during both periods, pre-pandemic and pandemic. Nonetheless, we find that the psychosocial risk factors change when we analyse the pre-pandemic and pandemic results. During the period before the pandemic, the psychosocial risk factors that were most commonly reported included the demanding pace of work, long working hours, and emotional demands. Through the pandemic, the most pronounced psychosocial risk factors were work relationships, employment relationships, and ethical and values conflicts. Therefore, research in this domain is essential to understanding psychosocial risk factors and assessing the less obvious links between work and health.